2018
DOI: 10.1186/s12888-018-1613-2
|View full text |Cite
|
Sign up to set email alerts
|

The power of support from companion animals for people living with mental health problems: a systematic review and narrative synthesis of the evidence

Abstract: BackgroundThere is increasing recognition of the therapeutic function pets can play in relation to mental health. However, there has been no systematic review of the evidence related to the comprehensive role of companion animals and how pets might contribute to the work associated with managing a long-term mental health condition. The aim of this study was to explore the extent, nature and quality of the evidence implicating the role and utility of pet ownership for people living with a mental health conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(208 citation statements)
references
References 37 publications
15
181
0
12
Order By: Relevance
“…Connection with pets provides benefits to those with mental health problems by offering emotional support [11]. Moreover, pet ownership is a modifiable environmental factor [12,13] because we can choose whether we own pets or not. However, the results of previous studies have been controversial, and a recent systematic review showed there is a shortage of high-quality and longitudinal studies that consider probable differences among different species [14].…”
Section: Introductionmentioning
confidence: 99%
“…Connection with pets provides benefits to those with mental health problems by offering emotional support [11]. Moreover, pet ownership is a modifiable environmental factor [12,13] because we can choose whether we own pets or not. However, the results of previous studies have been controversial, and a recent systematic review showed there is a shortage of high-quality and longitudinal studies that consider probable differences among different species [14].…”
Section: Introductionmentioning
confidence: 99%
“…Though reliable quantitative data may be limited, qualitative studies incorporating ethnography, participant observation, and interviews have repeatedly demonstrated the importance of companion animals in people's lives (Brooks et al 2018;Reisbig et al 2017;Charles 2016;Brooks et al 2016Brooks et al , 2018Maharaj and Haney 2014;Cavanaugh et al 2008). However, broad conclusions are typically limited when looking at qualitative studies, which tend to use smaller sample sizes, case studies, or a particular social setting to focus on describing and understanding specific experiences and social phenomena, rather than counting and measuring large-scale numerical data.…”
Section: Family According To Whom?mentioning
confidence: 99%
“…Personal communities of social support can range from members who are healthcare professionals, family, friends, community groups, objects (e.g. a bicycle), or even pets, which have been known to provide emotional support . A personal community which represents a diverse range of relationships and network member type (including so called ‘weak ties’) can be especially beneficial; for example, network members can be distributors of health literacy .…”
Section: Introductionmentioning
confidence: 99%